Cognitive training-induced short-term functional and long-term structural plastic change is related to gains in global cognition in healthy older adults: a pilot study - Lampit, Amit; Hallock, Harry; Suo, Chao; Naismith, Sharon L.; Valenzuela, Michael (Frontiers in Aging Neuroscience, 2015)
Computerized cognitive training (CCT) is a safe and inexpensive intervention to enhance cognitive performance in the elderly. However, the neural underpinning of CCT-induced effects and the timecourse by which such neural changes occur are unknown. Here, we report on results from a pilot study of healthy older adults who underwent three 1-hour weekly sessions of either multidomain CCT program (n = 7) or an active control intervention (n = 5) over 12 weeks. Multimodal magnetic resonance imaging (MRI) scans and cognitive assessments were performed at baseline and after 9 and 36 hours of training. Voxel-based structural analysis revealed a significant Group × Time interaction in the right postcentral gyrus indicating increased gray matter density in the CCT group compared to active control at both follow-ups. Across the entire sample, there were significant positive correlations between changes in the postcentral gyrus and change in global cognition after 36 hours of training. A post-hoc vertex-based analysis found a significant between-group difference in rate of thickness change between baseline and post-training in the left fusiform gyrus, as well as a large cluster in the right parietal lobe covering the supramarginal and postcentral gyri. Resting-state functional connectivity between the posterior cingulate and the superior frontal gyrus, and between the right hippocampus and the superior temporal gyrus significantly differed between the two groups after 9 hours of training and correlated with cognitive change post-training. No significant interactions were found for any of the spectroscopy and diffusion tensor imaging data. Though preliminary, our results suggest that functional change may precede structural and cognitive change, and that about one-half of the structural change occurs within the first nine hours of training. Future studies are required to determine the role of these brain changes in the mechanisms underlying CCT-induced cognitive effects.